2018
DOI: 10.1055/a-0792-1340
|View full text |Cite
|
Sign up to set email alerts
|

The Associations Between CYP2D6 Metabolizer Status and Pharmacokinetics and Clinical Outcomes of Venlafaxine: A Systematic Review and Meta-Analysis

Abstract: Background The association between CYP2D6 metabolizer status and clinical outcomes of venlafaxine was extensively investigated previously, but no widely accepted conclusion has been reached so far. To obtain a more precise estimation of the association, a systematic review by meta-analysis was conducted in the present study. Methods The PubMed, EMBASE, Cochrane Library, Chinese National Knowledge Infrastructure, Technology of Chongqing, and Wan Fang Database were searched for eligible studies up to August 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
6
1
Order By: Relevance
“…ODV is considered to have an antidepressant effect similar to that of VEN. 22,23 CYP2D6 is an enzyme with high affinity and low volume, which dominates the VEN metabolism; 17 its activity is considered to be a major intrinsic factor in the pharmacokinetics of VEN, 11 but it is speculated that the clinical significance of altering the activity of CYP2D6 is limited. 24 Both vonoprazan and VEN are substrates of CYP2D6.…”
mentioning
confidence: 99%
“…ODV is considered to have an antidepressant effect similar to that of VEN. 22,23 CYP2D6 is an enzyme with high affinity and low volume, which dominates the VEN metabolism; 17 its activity is considered to be a major intrinsic factor in the pharmacokinetics of VEN, 11 but it is speculated that the clinical significance of altering the activity of CYP2D6 is limited. 24 Both vonoprazan and VEN are substrates of CYP2D6.…”
mentioning
confidence: 99%
“…Our findings are consistent with the results of previous PK studies that have reported altered plasma levels of VEN among different CYP2D6 metabolizers. 12,[31][32][33][34][35][36] However, in studies that reported O-desmethylvenlafaxine exposure, younger individuals with lower CYP2D6 activity also had lower O-desmethylvenlafaxine exposure. 32,34 By contrast, in our study of older adults, no Notably, all metabolizer groups had a wide variety range of Odesmethylvenlafaxine exposure at both lower dosages and higher dosages (Figures 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…Correspondingly, in these previous studies, there were no differences in active moiety concentrations between different groups of CYP2D6 metabolizers and we observed significantly higher active moiety exposure in CYP2D6 PMs. 12,37,38 The discrepancies of findings may come from differences in methods to classify CYP2D6 metabolizers. Some studies simply use VEN/Odesmethylvenlafaxine level ratio instead of determining CYP2D6 metabolizer status based on genotyping results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have indicated significant intra- and inter-individual pharmacokinetic variability for VEN and ODV. The influences of sex, age, gene polymorphism (CYP2D6, CYP2C19) and comedications (e.g., valproic acid, doxepin, trimipramine, quetiapine) have been previously reported ( Klamerus et al, 1996 ; McAlpine et al, 2011 ; Paulzen et al, 2018a ; Paulzen et al, 2018b ; Lin et al, 2018 ; Kowalewski et al, 2019 ; Wang et al, 2020 ). However, studies exploring these effects on dose and concentration have shown inconsistent results and mixed effects.…”
Section: Introductionmentioning
confidence: 94%